Sustainable Machining - Davim, J. Paulo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book provides an overview on current sustainable machining. Its chapters cover the concept in economic, social and environmental dimensions. It provides the reader with proper ways to handle several pollutants produced during the machining process. The book is useful on both undergraduate and postgraduate levels and it is of interest to all those working with manufacturing and machining technology.
Ceramic cutting tools -- Chip recycling -- Cryogenic cooling -- Cutting energy -- Cutting fluids -- Cutting forces -- Environmentally friendly machining -- Minimal quantity of lubrication (MQL) -- Nanofluids -- Near dry machining -- Self-lubricating tools -- Tool life and wear.
Keywords: Manufactures; Sustainability; Coatings; Tribology; Corrosion and anti-corrosives.; Machines, Tools, Processes; Sustainability; Coatings; Tribology; Corrosion